2020
DOI: 10.1111/cch.12739
|View full text |Cite
|
Sign up to set email alerts
|

Parentally reported barriers to seeking help and advice for child sleep from healthcare professionals

Abstract: Background Healthcare professionals (HCPs), largely doctors, paediatricians, health visitors, midwives, and practice nurses, are in a good position to provide information, help, advice, or guidance to parents for child sleep. However, evidence suggests that there is a gap between the number of parents who desire assistance from HCPs and those that make use of these sources, yet very little is known about the reason for this apparent disparity. The aim of this study was to understand the barriers reported by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that patients have a need for support for their sleep and fatigue symptoms after active treatment has ended [ 4 , 56 , 57 ]. However, they often experience barriers with reporting sleep problems to their healthcare professional [ 58 ]. Therefore, active assessment—for example, by using patient-reported outcome measures (PROMs)—might help to recognize symptoms and incorporate fatigue–insomnia management within routine clinical care [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients have a need for support for their sleep and fatigue symptoms after active treatment has ended [ 4 , 56 , 57 ]. However, they often experience barriers with reporting sleep problems to their healthcare professional [ 58 ]. Therefore, active assessment—for example, by using patient-reported outcome measures (PROMs)—might help to recognize symptoms and incorporate fatigue–insomnia management within routine clinical care [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some parents who feel unsure or less trusting of their instincts, report feeling uncertain as to whether their infants' sleep is problematic (Hsu et al, 2017) and subsequently feel less confident in managing their child's sleep (Mindell, Sadeh, et al, 2015; Owens & Jones, 2011; Owens et al, 2011; Schreck & Richdale, 2011). In these instances, parents are more likely to seek and adhere to advice provided by healthcare professionals (G. Cook, Appleton, & Wiggs, 2020; Hsu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has predominantly focused on parental use of formal healthcare resources (Blunden et al, 2004 ; Cook et al, 2020 ; Hsu et al, 2017 ; Morrell, 1999 ), yet parents may also use other resources and so this emphasis may underrepresent the proportion of parents who seek help and how they approach doing so. Only a few studies have explored help‐seeking in a UK sample (Cook et al, 2020 ; Morrell, 1999 ). For example, Morrell ( 1999 ) explored advice seeking in mothers of 13–16 month olds.…”
Section: Introductionmentioning
confidence: 99%
“…However, only help‐seeking from formal healthcare resources, such as doctors or HVs, was explored and it remains unclear why some mothers who perceived their child to have a CSP had not sought professional help or if mothers had made use of sources other than HCPs. Recent studies have suggested that some parents have concerns about using HCPs for advice or support around child sleep due to a perceived lack of HCPs' knowledge or training (Cook et al, 2020 ; Hatton & Gardani, 2018 ). There remains a lack of evidence from the UK regarding what resources parents use and what factors encourage or cause parents to have reservations about the use of resources for child sleep.…”
Section: Introductionmentioning
confidence: 99%